Bidirectional movement of aphid parasitoids (Braconidae: Aphidiinae) between crops and non-crop plants in agroecosystems of central Argentina - Zumoffen, Leticia; Signorini Porchiett, Marcelo Lisandro; Salvo, Silvia Adriana (2018)
The movement of predators and parasitoids between natural and cultivated habitats is a common process in agroecosystems, which may be affected by different biotic and abiotic factors, mostly related to the availability of resources. Here, through a broad approach, we aimed to obtain an overview of factors affecting the bidirectional movement of aphid parasitoids (Braconidae: Aphidiinae) across cultivated habitats and their natural vegetated borders. Using bidirectional flight traps, we measured the number of parasitoids moving from borders to crops and vice versa, in fields of three common crop species (alfalfa, oat and wheat) in the Pampean region, Santa Fe, Argentina. The effects of the abundance of aphid prey, abundance and richness of flowers in both habitats, as well as temperature and wind speed on parasitoid movement, were assessed through generalized mixed models, considering sampling date and field as random factors. The relationship between parasitism percentages and parasitoid movement from the borders to the crops was explored separately for three pest aphid species: Aphis craccivora Koch, Rhopalosiphum padi (L.) and Schizaphis graminum (Rondani). Overall, we found a prevalence of parasitoids moving in the border-crop direction, mainly in wheat and alfalfa crops. Aphid abundance in the arrival habitat affected parasitoid movement in both directions. A link between parasitoid movement and parasitism percentages was observed for the aphid species S. graminum in wheat, suggesting a beneficial role of natural vegetation in pest control.